Analysis of dynamic characteristics of spiral groove liquid film seal under thermal–fluid–solid coupling. Issue 6 (10th August 2021) - Yu, Bo; Hao, Muming; Xinhui, Sun; Wang, Zengli; Fuyu, Liu; Yongfan, Li
Abstract : Purpose: The purpose of this paper is to investigate the dynamic characteristics of spiral groove liquid film seal under the effect of thermal–fluid–solid coupling. Design/methodology/approach: The dynamic analysis model of spiral groove liquid film seal under the effect of thermal–fluid–solid coupling was established by perturbation method. The steady-state and perturbation Reynolds equations were solved, and the steady-state sealing performance and dynamic characteristic coefficients of the liquid film were obtained. Findings: Compared with the liquid film without coupling method, a divergent seal gap is formed between the seal rings under the effect of thermal–fluid–solid coupling, the minimum liquid film thickness decreases, the dynamic stiffness and damping coefficients of the liquid film are increased and the thermoelastic deformation of the end-face improves the dynamic performance of the liquid film seal. Originality/value: The dynamic characteristics of the spiral groove liquid film seal under the effect of thermal–fluid–solid coupling are studied, which provides a theoretical reference for optimizing the dynamic performance of the non-contacting liquid film seal.